EFFECT OF ANTIHYPERTENSIVE THERAPY BASED ON NEW METHOD OF INDIVIDUAL CHOICE OF DRUGS ON LEFT VENTRICULAR HYPERTROPHY IN ELDERLY PATIENTS - K. I. Pshenichkin (Столичная издательская компания, 2015)
Aim. To study the effects of antihypertensive therapy based on consideration of individual heart rhythm variability (HRV) on left ventricular hypertrophy (LVH) in hypertensive elderly patients. Material and methods. 60 hypertensive elderly patients with LVH were included in the study. They were split in two groups (30 people in each one). Patients of the group-I had common antihypertensive therapy. Patients of group-II received medications prescribed with consideration of individual heart rate variability. Holter monitoring with analysis of HRV, 24-hour blood pressure monitoring and ultrasonography were conducted initially and 18 months after treatment beginning. Results. BP control was reached in the majority of patients of both groups. The patients of group-II in comparison with patients of group-I had reduction of low- high frequency power ratio (LF/HF) and higher rate of LVH reduction. Relationship between LVH dynamics and ratio LF/HF was found. Conclusion. Arterial hypertension therapy considering individual HRV contributes in LVH reduction in elderly patients.